The tropomyosin 3.1/3.2 inhibitor ATM-3507 alters B-cell actin dynamics and impairs the growth and motility of diffuse large B-cell lymphoma cell lines - Bedi, Abhishek; Choi, Kate; Iskierski, Alyssa; Gold, Michael R. (Frontiers in Immunology, 2025)
IntroductionBy stabilizing actin filaments and recruiting non-muscle myosin II, the closely related tropomyosin (Tpm) isoforms Tpm3.1 and Tpm3.2 support actin-dependent processes including membrane dynamics, cell migration, and cytokinesis. Actin dynamics are essential for B cell function, but the roles of Tpm3.1 and 3.2 (collectively termed Tpm3.1/3.2) in B cells have not been explored. Moreover, new treatments are needed to limit the growth and dissemination of diffuse large B-cell lymphoma (DLBCL), the most prevalent B-cell malignancy.MethodsTo test whether Tpm3.1/3.2 is essential for B-cell actin dynamics and could be a target for treating DLBCL, we employed ATM-3507, a compound that selectively interferes with Tpm3.1/3.2 function.ResultsWe show that ATM-3507 treatment inhibited B-cell receptor-induced formation of the peripheral ring of branched actin that drives cell spreading and also prevented the formation of actomyosin arcs at the inner face of the peripheral actin ring. Tpm3.1/3.2 localizes to these structures during B-cell spreading. Treating DLBCL cell lines with ATM-3507 inhibited cell growth and caused the cells to accumulate in the G2/M phase of the cell cycle. Furthermore, ATM-3507 markedly reduced CXCL12-stimulated chemotaxis and integrin-dependent motility of DLBCL cell lines on fibronectin.ConclusionTpm3.1/3.2 orchestrates key actin-driven processes in B cells, and drugs that target Tpm3.1/3.2 may be useful adjuncts for treating DLBCL.